Spirituality in Psychiatric Nursing: A Concept Analysis. (January 2021) - Clark, Michelle; Emerson, Amanda
BACKGROUND: There is robust literature on spirituality in nursing. Despite the unique needs of those with serious mental illness, there has been little exploration of spirituality in the context of nursing care for this population. Lacking a well-defined concept of spirituality in psychiatric care, mental health nurses often struggle to provide optimal, holistic care.AIMS: The aim of this concept analysis was to review definitions and descriptions of spirituality in the psychiatric nursing literature to synthesize a usable definition to inform practice and provide a basis for future study.METHOD: Beth Rodgers's evolutionary concept analysis method was followed to inductively derive a definition of spirituality in psychiatric nursing care. Steps included identification of the concept, setting, and sample; synthesis of key attributes, antecedents, and consequences from the literature; and a discussion of implications. A search in the psychiatric nursing literature (1998-2019) included literature reviews, case studies, concept analyses, qualitative interview studies, and quantitative survey research.RESULTS: Spirituality in psychiatric nursing was defined by attributes of a search for life meaning and purpose and a sense of connectedness. Spirituality in the practice of psychiatric nursing was a result of value-influenced thinking and a capability for interaction with others. Consequences included consolation and positive or negative coping.CONCLUSIONS: A clearly defined concept of spirituality in psychiatric nursing can provide a basis for clinical confidence for nurses in identifying patient spiritual needs and choosing appropriate interventions to support those needs.